Advanced ceramics in the SnO2–ZnO binary system. Issue 3 (April 2015) - Mihaiu, Susana; Toader, Alexandra; Atkinson, Irina; Mocioiu, Oana Cătălina; Hornoiu, Cristian; Teodorescu, Valentin Serban; Zaharescu, Maria
Abstract: In the present work, we report a systematic study of the phase formation and sintering ability of different oxide compositions in the SnO2 –ZnO binary system using solid state reactions. For some selected compositions mechanically activated powders were also investigated. Structural and morphological characterizations of the samples were performed by X-ray diffraction (XRD), FT-IR Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). Only the formation of Zn2 SnO4 binary compound was revealed in the experimental conditions. Based on the structural results the subsolidus equilibrium phase diagram was established. The sintering ability of the studied samples was also determined, establishing the compositions domains of obtaining dense or porous ceramics. The investigation by impedance spectroscopy in the 300–600 K temperature range shows that all studied samples exhibit n-type semiconductor behavior with low values of the activation energy (0.18–0.34 eV).